The adoption of a Climate Disaster Resilience Index in Chennai, India. Issue 3 (July 2014) - Joerin, Jonas; Shaw, Rajib; Takeuchi, Yukiko; Krishnamurthy, Ramasamy
<x xml:space="preserve">Abstract</x> Results derived from the Climate Disaster Resilience Index (CDRI)—consisting of five dimensions (economic, institutional, natural, physical, and social), 25 parameters, and 125 variables—reflect the abilities of people and institutions to respond to potential climate‐related disasters in Chennai, India. The findings of this assessment, applied in the 10 administrative zones of the city, reveal that communities living in the northern and older parts of Chennai have lower overall resilience as compared to the flourishing areas (vis‐à‐vis economic growth and population) along the urban fringes. The higher resilience of communities along the urban fringes suggests that urbanisation may not necessarily lead to a deterioration of basic urban services, such as electricity, housing, and water. This indication is confirmed by a strong statistical correlation between physical resilience and population growth in Chennai. The identification of the resilience of different urban areas of Chennai has the potential to support future planning decisions on the city's scheduled expansion.